Metagenomics of black grains: new highlights in the understanding of eumycetoma. (15th January 2021) - Santona, Antonella; Mhmoud, Najwa A; Siddig, Emmanuel Edwar; Deligios, Massimo; Fiamma, Maura; Bakhiet, Sahar Mubarak; Barac, Aleksandra; Paglietti, Bianca; Rubino, Salvatore; Fahal, Ahmed Hassan
Abstract: Background: Eumycetoma is a chronic subcutaneous granulomatous disease that is endemic in Sudan and other countries. It can be caused by eight different fungal orders. The gold standard diagnostic test is culture, however, culture-independent methods such as imaging, histopathological and molecular techniques can support diagnosis, especially in cases of negative cultures. Methods: The amplicon-based internal transcribed spacer 2 metagenomic technique was used to study black grains isolated from 14 tissue biopsies from patients with mycetoma. Furthermore, mycological culture and surgical biopsy histopathological examinations of grains were performed. Results: Madurella mycetomatis (n=5) and Falciformispora spp. (n=4) organisms were identified by culture and confirmed by metagenomics. Metagenomics recognised, at the species level, Falciformispora as Falciformispora tompkinsii (n=3) and Falciformispora senegalensis (n=1), while in culture-negative cases (n=5), Madurella mycetomatis (n=3), Falciformispora senegalensis (n=1) and Fusarium spp. (n=1) were identified. Interestingly, the metagenomics results showed a 'consortium' of different fungi in each sample, mainly Ascomycota phylum, including various species associated with eumycetoma. The microbial co-occurrence in eumycetoma showed the co-presence of Madurella with Trichoderma, Chaetomium, Malasseziales and Sordariales spp., while Falciformispora co-presented with Inocybe and Alternaria and was in mutual exclusion with Subramaniula, Aspergillus and Trichothecium . Conclusion: Metagenomics provides new insights into the aetiology of eumycetoma in samples with negative culture and into the diversity and complexity of grains mycobiota, calling into question the accuracy of traditional culture for the identification of causative agents.